The Impact of China-Africa Trade on Industries in Africa: A Case Study of FOCAC and BRI - Mbona, Reginald Masimba (Business and Economic Research, 2021)
<span style="color: #000000; font-family: Verdana, Arial, Helvetica, sans-serif; font-size: 10px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: start; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial; display: inline !important; float: none;">Over the last two decades, the trade between Africa and China has grown significantly but there is still a debate on how local industries in Africa are being affected. Two key foreign policies, FOCAC and BRI, by China are the foundations on which the trade is done with its African partners. This study aims to assess which industries in Africa are being affected by these Chinese-led foreign trade policies and the significance of that impact. Using panel data, the study examines the effect of the FOCAC era and the FOCAC+BRI era on the energy, agriculture, mining, manufacturing, and technology industries for six partners. The results from the analysis showed that imports positively affect the agriculture and the energy sectors while the manufacturing industry is negatively affected by imported goods. On the other hand, exports have shown a positive impact on the mining sector. However, the agriculture industry is still struggling to have positive gains from exports. The findings of this study are important as the continent works towards "One Africa" which seeks to promote sustainable development of the continent. Also, the study focuses on specific industries that are significant to the economic growth of these countries as shown by their positive relationship with the GDP of these nations.